2016
DOI: 10.1007/s00299-016-2079-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel cadmium-regulated Yellow Stripe-Like transporter (SnYSL3) in Solanum nigrum

Abstract: SnYSL3 encodes a plasma-localized transporter delivering various metal-nicotianamine complexes. The expression of SnYSL3 is up-regulated by excess Cd, suggesting an important role for SnYSL3 in response to Cd stress. The Yellow Stripe-Like (YSL) transporters have been proposed to participate in metal uptake and long-range transport in model plants. In this study, we isolated and characterized a novel member of the YSL gene family, SnYSL3, from the cadmium hyperaccumulator Solanum nigrum. SnYSL3 was constitutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 77 publications
3
31
0
Order By: Relevance
“…Cd mediated the expression of YSL3 and YSL7 , suggesting Cd affected Fe transport in the plant. Previous study also found that YSL3 in Solanum nigrum and YSL7 in Brassica juncea were induced by Cd as well 58 , 59 . However, it remains unknown whether YSL family genes are involved in transport of Cd-NA complexes transport, and further study must be conducted to analyze the function of YSL genes under Cd stress.…”
Section: Discussionmentioning
confidence: 62%
“…Cd mediated the expression of YSL3 and YSL7 , suggesting Cd affected Fe transport in the plant. Previous study also found that YSL3 in Solanum nigrum and YSL7 in Brassica juncea were induced by Cd as well 58 , 59 . However, it remains unknown whether YSL family genes are involved in transport of Cd-NA complexes transport, and further study must be conducted to analyze the function of YSL genes under Cd stress.…”
Section: Discussionmentioning
confidence: 62%
“…Cadmium is a non-essential element; thus, plants have not developed a specialized uptake system for its absorption. Instead, Cd enters plants and is transported across various membranes by other metal transporters [40][41][42][43] or non-selective cation channels [44,45]. This results in a competition with acquisition of some essential metals.…”
Section: Cadmium Impact On Plant Growth and Performancementioning
confidence: 99%
“…Here, Fe(III)-phytosiderophore complexes (Fe(III)-PS) are taken into the root cells by yellow stripe 1 or yellow stripe-like 1 (YS1/YSL1) transporters identified in maize [75] and barley [76]. In chelated form, Cd may also be transported by YSL (yellow stripe-like 1) proteins such as OsYSL2 in rice and SnYSL3 in Solanum nigrum [41,77]. Plants belonging to Strategy I have the ability to transport Cd across plasma membrane by the same mechanisms employed for Fe 2+ transport.…”
Section: Uptake By Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Feng et al (2017), Metal-nicotianamine transporter 3 (YSL 3 ) gene expression increased significantly in response to excess cadmium in Solanum nigrum. On the other hand, the response of genes to metal-deficient, metalsufficient or metal-excess conditions is partially depending on the plant species (Morkunas et al 2018).…”
mentioning
confidence: 99%